How Does the World Deal with E-waste? Its Management and Analysis - Siddhi V. Kulkarni (International Journal of Environmental Noise and Pollution Control, 2023)
There are numerous electrical devices used daily. Whether we do it knowingly or unknowingly, we always appreciate how much easier life is as a result. But as we all know that everything nice eventually comes to an end, these gadgets inevitably stop working and are wasted. One of them claims that electronic garbage, or “E-waste”, is a global issue that is only becoming worse. A significant buildup of e-waste is caused by the advent of newer technology and the exponential growth of electronic consumption. For effective e-waste management, there is a need for a tool that both individuals and companies can use. Thus, the term “e-waste” is considered. In this study, we will see a brief study of how the world deals with this electronic waste problem. And how does the world analyze this waste? And help our earth become a better place in various ways.
Keywords: E-waste; World Health Organization; analyst; garbage; machines